New Developments in the Production and Recovery of Amino Acids, Vitamins, and Metabolites from Microbial Sources - Shukla P.; Srivastava P.; Mishra A. (My University, 2025)
In the food, chemical, and pharmaceutical industries, macromolecules like amino acids, vitamins, and metabolites generated by microorganisms using renewable feedstocks are significant due to their low cost and sustainability. In addition to their conventional uses, these are also employed in emerging research fields like the production of bioplastics and aesthetic surgeries. These macromolecules can be manufactured commercially using chemical and biological processes, which is an efficient and environmentally benign technique. Microbial solid cell factories with exceptional resistance to extreme pH conditions, large concentrations of metabolites, and lignocellulosic inhibitors are required for an economically feasible fermentation process. Strain improvement and metabolic engineering are two techniques that can be used to create strains with high productivity. This chapter discusses the biosynthetic pathways, substrates, strain improvement, and upstream techniques for methionine L-glutamate, L-lysine, vitamins B2 and B12, coenzyme Q10 or ubiquinone, lactic acid, itaconic acid, and hyaluronic acid as well as their market perspective and budding challenges. © The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2023.